Dabartinės lietuvių literatūrinės kalbos adjektyvinių pranašumo konstrukcijų semantiniai bei struktūriniai ypatumai - Janulienė, Aušra (Kalbotyra, 1987)
An attempt is made to describe the semantic and structural peculiarities of Lithuanian comparative constructions of superiority. Special attention is paid to the presuppositional properties and usage peculiarities of the constructions.